DAMPAK PENYULUHAN PADA PENGETAHUAN MASYARAKAT TERHADAP PEMILIHAN DAN PENGGUNAAN OBAT BATUK SWAMEDIKASI DI KECAMATAN MALALAYANG - Meriati, Ni Wayan Eka; Goenawi, Lily Ranty; Wiyono, Weny (UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACTThe efforts of society to heal theirself is called self-medication or swamedikasi. Selfmediacationis usually used to overcome the complaints and minor illnesses such the cough.The cough medicine can not be samed with all kinds of cough. This research is aimed toidentify the impact of socialization on public knowledge toward the selection and the use ofself-medication (swamedikasi ) cough medicine in Malalayang subdistrict. This is anexperimental research with one group pretest-postest design. The collecting process ofsample was done by random sampling technique with 150 respondences. The instrument ofthis research is questioner about cough medicine knowledge comprises of 18 questions andleaflet as the media. Based on the acquired information, the averagely score of publicknowledge in pretest is 64,55 and in postest is 90,11 with probability value (p) = 0.000 < (Î±)0.05, so H0 is rejected. It shows that there is an influence of socialization toward the selectionand the use of self-medication ( swamedikasi ) cough medicine in Malalayang subdistrict.There is a real difference averagely about the public knowledge before and after socialization.Key words: Socialization, Cough medicine, Self-medication ( swamedikasi )